2003
DOI: 10.1088/0953-8984/15/17/305
|View full text |Cite
|
Sign up to set email alerts
|

Photoexcitation electron paramagnetic resonance studies on nickel-related defects in diamond

Abstract: Measurements of the electron paramagnetic resonance (EPR) upon photoexcitation are reported on Ni defects in diamonds grown with Nicontaining solvent/catalysts. The temperature dependence of the W8 EPR spectrum photoquenching shows that the relaxation of substitutional Ni − s upon electron ionization is very small, corroborating the interpretation that the previously reported photoinduced effects with thresholds at 2.5 and 3.0 eV correspond to two complementary photoionization transitions involving Ni s . Phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…However, up to now research was mainly focused on nickel (Ni)‐related defect centres in synthetic diamonds grown by the HPHT method 13–19. A practical operation of quantum devices, based on nickel–nitrogen centres, requires the reproducible generation of nickel–nitrogen centres in diamond nanocrystals, as well as in high quality single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…However, up to now research was mainly focused on nickel (Ni)‐related defect centres in synthetic diamonds grown by the HPHT method 13–19. A practical operation of quantum devices, based on nickel–nitrogen centres, requires the reproducible generation of nickel–nitrogen centres in diamond nanocrystals, as well as in high quality single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Through the demonstration of electron paramagnetic resonance, photoluminesence and optical absorption, numerous nickel-related defects has been identified in the diamond, including substitutional nickel 1 , nickel-vacancy 2 and nickel-vacancy-nitrogen complexes (NE centers) 3 . Several theoretical approaches have been used to investigate these nickel-related defects' structural and electronic properties [4][5][6] . Experimentally, it has been reported that NE8 center can be an excellent infrared single-photon source at room temperature [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…There are rare reports on the synthesis of hexagonal SiC nanowires [145,146]. The preferential growth direction of 3C SiC nanowire can be manipulated to fall along the [111], [100] and [112] directions.…”
Section: Resultsmentioning
confidence: 99%
“…[111] [112] [111] [110] C H Si Since the characteristics of SiC nanowire can be controlled with such a high degree of freedom, quite a bit of choice will be available when we introduce the nickel dopant into the nanowire. We need to determine the polytypes and crystal direction of SiC nanowire before starting calculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation